STIE Bina Karya Students’ Financial Literacy - Haratika, Haya; Purba, Anita; Suryaman, Restu A (Community Service Progress, 2023)
Financial litarcy is essential to be implemented seriously in individual life. The good financial management will lead someone into prosperity and the poor financial management will lead into financial collapse. Education background affects someone’s ability in managing their expenses. The higher education, the better understanding on financial literacy . The purpose of this study was to gain the information from the 8th semester college students year 2023 STIE Bina Karya about their financial litearcy. This study implemented qualitative method which took 36 informants who represent each class. The researcher distributed open-ended questions through online based questionaire to obtain the data. The data then analyzed by utilyzing thematic analysis. The findings of this study were STIE Bina Karya the 8th semester students knew well about financial literacy, they have implemented the four parts of financial literacy those were: personal financial management, bank deposits, insurance, and stock investment. The implication of this research findings was to enhance the number of college students’ understanding of financial literacy and to inform the benefits after implementing the correct financial literacy.